Respuesta :
Answer:
x=2 x=-3
Step-by-step explanation:
4x2+3x=24-x
Subtract 24 from each side
4x^2 +3x -24 = 24-24 -x
4x^2 +3x -24 = -x
Add x to each side
4x^2 +3x+x -24 = -x+x
4x^2 +4x -24 = 0
Factor out a 4
4(x^2 +x -6) = 0
Divide by 4
x^2 +x -6 =0
Factor
What 2 numbers multiply to -6 and add to 1
-2*3 = -6
-2+3 =1
(x-2) (x+3) =0
Using the zero product property
x-2 =0 x+3 =0
x-2+2=0+2 x+3-3=0-3
x=2 x=-3
Answer:x=-3 , x = 2
Step-by-step explanation:
First move the expression ( 24-x) to the left.
This gives us 4x^2+3x+24-x.
Collect the like terms which gives us 4x^2+4x+24
4x^2+4x-24 = 0. Divide both sides by 4.
x^2 + x-6 = 0
Factorise the expression so you get (x+3)(x-2)=0
Solve the equations x+3 = 0 and x-2=0
The final solutions are x=-3 and x=2.